2015
DOI: 10.1186/s12864-015-1473-9
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variations in high and low fertility breeding boars

Abstract: BackgroundIn this study we applied the extreme groups/selective genotyping approach for identifying copy number variations in high and low fertility breeding boars. The fertility indicator was the calculated Direct Boar Effect on litter size (DBE) that was obtained as a by-product of the national genetic evaluation for litter size (BLUP). The two groups of animals had DBE values at the upper (high fertility) and lower (low fertility) end of the distribution from a population of more than 38,000 boars. Animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…In order to extend the panel of the 21 tested animals, of which we had no specific fertility information available other than their general good reproductive health, 10 additional unrelated boars with known fertility status (five High-fertility and five Low-fertility) were chosen from a separate population [ 23 ]. The fertility indicator parameter was the Direct Boar Effect on litter size (DBE) that is the number of piglets the given boar produces in average per litter ( S3 Table ) as compared to the overall average of the population and corrected for all identified environmental effects and breeding values of their mate [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to extend the panel of the 21 tested animals, of which we had no specific fertility information available other than their general good reproductive health, 10 additional unrelated boars with known fertility status (five High-fertility and five Low-fertility) were chosen from a separate population [ 23 ]. The fertility indicator parameter was the Direct Boar Effect on litter size (DBE) that is the number of piglets the given boar produces in average per litter ( S3 Table ) as compared to the overall average of the population and corrected for all identified environmental effects and breeding values of their mate [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genome-wide (autosomal) CNVs were estimated from the normalized signal intensity data (logR ratio) using the SNP and Variation Suite (SVS version 8.4.3., GoldenHelix Inc.), as described earlier in detail [Revay et al, 2015]. Briefly, quality control steps of testing for outlier noise or genomic waves by investigating the derivative logR ratio distribution and batch effects with principal component analysis were followed by the detection of CNVs using the Univariate-CNAM segmentation algorithm in SVS.…”
Section: Methodsmentioning
confidence: 99%
“…They are also associated with common traits and various diseases such as Crohn's disease, rheumatoid arthritis and diabetes (Fontanesi et al., ; WTCCC, ). The determination of CNV has become increasingly important for the evaluation of genomic traits in domestic animals (Revay, Quach, Maignel, Sullivan, & King, ; Xu et al., ). Our previous study revealed that MTHFSD gene was identified in the CNVs region of Chinese Xiang pig genome by Illumina PorcineSNP60K BeadChip.…”
Section: Introductionmentioning
confidence: 99%
“…2010). The determination of CNV has become increasingly important for the evaluation of genomic traits in domestic animals (Revay, Quach, Maignel, Sullivan, & King, 2015;Xu et al, 2014). Our previous study revealed that MTHFSD gene was identified in the CNVs region of Chinese Xiang pig genome by Illumina PorcineSNP60K…”
Section: Introductionmentioning
confidence: 99%